A Nanohook‐Equipped Bionanocatalyst for Localized Near‐Infrared‐Enhanced Catalytic Bacterial Disinfection. Issue 8 (3rd January 2022) - Fan, Xin; Wu, Xizheng; Yang, Fan; Wang, Lei; Ludwig, Kai; Ma, Lang; Trampuz, Andrej; Cheng, Chong; Haag, Rainer
Abstract: Novel bionanocatalysts have opened a new era in fighting multidrug‐resistant (MDR) bacteria. They can kill bacteria by elevating the level of reactive oxygen species (ROS) in the presence of chemicals like H2 O2 . However, ROSs' ultrashort diffusion distance limit their bactericidal activity. We present a nanohook‐equipped bionanocatalyst (Ni@Co‐NC) with bacterial binding ability that shows robust ROS‐generating capacity under physiological H2 O2 levels. The Ni@Co‐NC's pH‐dependent performance confines its effects to the biofilm microenvironment, leaving healthy tissue unaffected. Furthermore, it can generate heat upon NIR laser irradiation, enhancing its catalytic performance while achieving heat ablation against bacteria. With the Ni@Co‐NC's synergistic effects, bacterial populations fall by >99.99 %. More surprisingly, the mature biofilm shows no recurrence after treatment with the Ni@Co‐NC, demonstrating its tremendous potential for treating MDR bacterial related infections. Abstract : A nanohook‐equipped bionanocatalyst can firstly hook to bacteria and biofilm, then catalyze H2 O2 to generate toxic hydroxyl radicals for localized disinfection. Upon the near‐infrared laser irradiation, the bionanocatalyst can generate heat, which simultaneously accelerates the catalytic therapy and enables the heat ablation against bacteria.